Change in organic molecule adhesion on α-alumina (sapphire) with change in NaCl and CaCl2 solution salinity - Juhl, K M S (Langmuir : the ACS journal of surfaces and colloids, 2014)
We investigated the adhesion of two functional groups to α-alumina as a model for the adsorption of organic molecules on clay minerals. Interactions between organic compounds and clay minerals play an important role in processes such as drinking water treatment, remediation of contaminated soil, oil recovery, and fabricating complicated nanomaterials, and there have been claims that organic compound-clay mineral interaction created the ordering that is necessary for the genesis of life. In many organisms, interaction between organic molecules and biominerals makes it possible to control the growth of bones, teeth, and shells. Adhesion of carboxylic acid, -COO(H), and pyridine, -C5H5N(H(+)), on the {0001} plane of α-alumina wafers has been investigated with atomic force microscopy (AFM) in chemical force mapping (CFM) mode. Both functional groups adhered to α-alumina in deionized water at pH < 5, and adhesion decreased as NaCl or CaCl2 concentration increased. X-ray photoelectron spectroscopy (XPS) showed that Na(+) and Ca(2+) adsorbed to the α-alumina surface at pH < 5, decreasing surface interaction with the carboxylic acid and pyridine groups. We interpret the results as evidence that the tips adhere to alumina through hydrogen bonding when only water is present. In solutions containing NaCl and CaCl2, cations are adsorbed but Cl(-) is not. When NaCl solutions are replaced by CaCl2, Ca(2+) replaces Na(+), but rinsing with ultrapure deionized water (pH 5.6) could not restore the original protonated surface. The results demonstrate that the alumina surface at pH 3 has a higher affinity for inorganic cations than for -COO(H) or -C5H5N(H(+)), in spite of the known positive surface charge of α-alumina {0001} wafers. These results demonstrate that solution salinity plays an important role in surface properties, controlling surface tension (i.e., contact angle) and adsorption affinity on α-alumina and, by analogy, on clay minerals